REVOLUTIONIZING NATIONAL INCOME THROUGH ISLAMIC ECONOMICS TO ACHIEVE GLOBAL JUSTICE - Arimbi, Tania (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Background: National income in Islamic economics integrates principles of distributive justice, halal economic activities, and social welfare, aligning with sharia principles. Conventional economic approaches to national income measurement, such as Gross National Product (GNP), often overlook equitable income distribution and environmental impacts. Knowledge Gap: However, there is a lack of comprehensive understanding regarding how national income is conceptualized and measured within the framework of Islamic economics. Aims: This study aims to bridge this gap by exploring the concept of national income from an Islamic economic perspective, emphasizing the role of sharia principles in economic management. Results: The research reveals that, unlike conventional approaches, Islamic economics measures national income through economic activities that comply with sharia, including consumption, investment, and international trade, with a strong emphasis on justice, social welfare, and support for the economically disadvantaged. The study also underscores that Islamic economics incorporates spiritual and humanitarian dimensions in assessing economic well-being. Novelty: This research provides a fresh contribution to the literature by highlighting the significance of integrating sharia principles into the conceptualization and measurement of national income, an area previously underexplored. Implications: The findings suggest that adopting an Islamic economic perspective on national income could lead to more sustainable and meaningful economic outcomes, promoting equitable distribution, avoiding riba (usury) and speculation, and prioritizing the welfare of the weak. This study underscores the potential of Islamic economic principles to contribute to more just and prosperous economic systems.